2020
DOI: 10.1016/j.neubiorev.2020.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal reorganisation in deafness: Mechanisms for functional preservation and functional change

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 145 publications
(183 reference statements)
3
49
0
Order By: Relevance
“…Overall, results from this study suggest different responses in deaf "auditory" temporal areas for executive and language processing. We have previously observed these shared functions, describing an overlap between working memory and language processing in superior temporal areas of deaf adults (Cardin et al, 2020b). By understanding the developmental trajectories of these changes we can move towards a unified theory of crossmodal plasticity.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Overall, results from this study suggest different responses in deaf "auditory" temporal areas for executive and language processing. We have previously observed these shared functions, describing an overlap between working memory and language processing in superior temporal areas of deaf adults (Cardin et al, 2020b). By understanding the developmental trajectories of these changes we can move towards a unified theory of crossmodal plasticity.…”
Section: Resultsmentioning
confidence: 85%
“…where these regions maintain their original computation but adapt to respond to a different sensory input (Lomber et al, 2010;Cardin et al, 2013;Bola et al, 2017;Benetti et al, 2017Benetti et al, , 2021. Other studies have suggested that sensory-deprived auditory regions are involved in higher-order cognitive functions, suggesting a functional change (see for a review Cardin et al, 2020b). Taking into account different mechanisms that can support all these findings…”
Section: The Auditory Cortex Of Deaf Individuals Is Recruited During mentioning
confidence: 95%
See 3 more Smart Citations